Acceptance Model of UTAUT2-Based Accounting Information System on The Shopeepay Digital Payment Application - Anggraeni, Annisa Fitri; Lestari, Lusi (Dinasti Research & Yayasan Dharma Indonesia Tercinta (DINASTI), 2025)
The effect of performance expectancy, effort expectancy, social influence, facilitating conditions, habit, and hedonic motivation on the use behavior of ShopeePay users in students of the Faculty of Economics and Business, Winaya Mukti University. The research uses a quantitative approach with a survey method. The research population is ShopeePay user students, with a sample of 100 respondents selected using the purposive sampling technique. Data analysis was carried out using multiple linear regression, t-test, F test, and determination coefficient. The results of the study show that social influence, habit, and hedonic motivation have a positive and significant effect on use behavior. On the other hand, performance expectancy, effort expectancy, and facilitating conditions had no significant effect on use behavior. Simultaneously, the six independent variables had a significant effect on use behavior with a Fcal value of 45.520 and an R Square value of 0.746. This shows that 74.6% of ShopeePay usage behavior can be explained by variables in the research model, while the rest is influenced by other factors outside the model. These findings show that usage habits, fun motivation, and social influence are the dominant factors in increasing the use of ShopeePay among students.